Improving Science Learning Outcomes for Class VII.B SMP Negeri 47 South Konawe Through the “Switch Partner” Technique - ernawati ernawati (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aims to improve student learning outcomes in science subjects through cooperative learning with the "Exchange Pairs" technique. This research was conducted at SMP Negeri 24 Konawe Selatan. The subjects studied were students of class VII.B totalling 32 students with details of 17 women and 15 men. Based on the data obtained from the results of research in two learning cycles, it can be explained as follows: 1) the results of 16 aspects of observing the management of learning activities in cycle II with perfect criteria, respectively 18.8%, 43.8% and 43.8 % are better when compared to the first cycle where the results obtained respectively 0%, 0% and 0%, 2) student achievement showed a very significant increase, wherein the second cycle eight students (25%) who scored with perfect criteria and 17 students (53.13%) who scored with reasonable criteria, when compared to the first cycle there were no students who scored with perfect criteria (0%) and six students (18.8%) who scored with reasonable criteria, and 3) the number of students who obtained a KKM score 65 in the second cycle of 32 students (100%) increased when compared to the first cycle of 20 students (62.5%). The conclusion is that using cooperative learning with the "Exchanging Pairs" technique can improve student learning outcomes in science subjects in class VII.B of SMP Negeri 24 Konawe Selatan.